Time-counting expressions as aspectual complex numerals - Di Sciullo, Anna Maria; Español-Echevarría, Manuel (Revista Letras, 2017)
We compare the syntactic and semantic properties of time-counting expressions to those of better studied counting systems, such as complex cardinal numerals (Kayne 2005, 2016; Ionin & Matushansky 2006; Stavrou & Terzi 2008; Di Sciullo 2012, 2015, a.o.). From a typological point of view, we will focus on Romance languages. We argue that time-counting expressions, as opposed to complex numerical expressions, may have specific aspectual properties. We observe first that time-counting expressions involve a “salient” reference time, henceforth SRT, on the basis of Italian and Spanish. We argue that this salient reference hour-time may denote either a time‑point or a time-interval. The time-point interpretation of the SRT gives rise to telic construals in some cases. The lack of SRT makes number phrases not interpretable as time denoting expressions. The telic construals usually involve locative or goal prepositions, such as a “to” in Italian, para “for” in Portuguese or to in English. On the other hand, time-interval interpretations of SRT are typical of time-counting expressions involving pseudo‑partitives in languages like Catalan. In these cases, the reference-time is not viewed as the endpoint of a telic interval. We also discuss telic cases similar to the pseudo-partitive ones in that they involve [quarter + minutes] constituents, but involving aspectual prepositional projections. We analyze time‑counting expressions in terms of extended prepositional projections including RelView categories, discussed in Cinque & Rizzi (2010) for the syntax-semantics of locative/directional prepositions, in order to formalize the spatial location of time. By doing so, we propose a unified account for the variety of Romance languages time-counting expressions.